Comprehensive analysis of Toxoplasma gondii migration routes and tissue dissemination in the host. - Carlos J Ramírez-Flores; Ricardo Mondragón-Flores (PLoS Neglected Tropical Diseases)
Toxoplasma gondii is a highly adaptable intracellular parasite capable of infecting a wide range of warm-blooded animals, including humans. Following the ingestion of cysts and oocysts, the parasites rapidly emerge and transmigrate through the bloodstream, initiating a complex infection process. Despite reports on the parasite's dissemination, the mechanisms behind its migration remain unclear. Recent advances using innovative 3D models and various host systems are beginning to shed light on the migratory routes and strategies employed by T. gondii. This review compiles current knowledge on the migration and dissemination of T. gondii, from its initial interactions in the gut to its invasion of immune-privileged organs. This review provides a comprehensive understanding of how T. gondii establishes its infection crossing the most impermeable biological barriers within the host.